PENGARUH INOVASI ORGANISASI TERHADAP KAPASITAS INOVASI TEKNOLOGI PADA PERUSAHAAN KONTRAKTOR - Merni Mega Anggawati; Adrian Azhar Wijanarko (Jurnal Bina Bangsa Ekonomika, 2024)
Organizational and technological innovation is a key factor that affects the performance of companies in the construction industry, especially towards increasing national economic development. This study aims to determine the influence of organizational innovation on the ability to innovate product and process technology. The research was conducted using a quantitative approach, adopting models by Camisón and Villar-López, and using organizational innovation studies by the OECD, Armbruster, and Prajogo and Sohal. The data was collected through surveys on construction companies and analyzed using linear regression to determine the relationship between variables. The results of the study show that organizational innovation has a positive influence on the ability to innovate technology in construction companies, both from the capacity of product and process technology innovation. The implications of the research show that companies are actively implementing new methods in management and operations so that they are better able to adopt and utilize the latest technology. This policy is able to contribute positively to improving the company's performance so that it not only improves operational efficiency but also strengthens the company's competitiveness in a highly competitive industry. The contribution of this research to the literature is to provide empirical evidence about the importance of organizational innovation in supporting technological innovation capabilities in the construction industry. The limitations of this study include a sample that is limited to one industry sector and may not be generalized to other sectors. The next direction of research is suggested to expand the scope of the sample and explore other variables that may affect the relationship between organizational innovation and technology. The conclusion of the study shows that organizational innovation has a positive relationship with the innovation capacity of employees, especially using the idea that organizational innovation and technology can create a more dynamic and responsive business environment to market changes and operational challenges. Thus, investment in organizational innovation and technology is not only a strategic choice but also a must for companies that want to survive and thrive in the long term.